2021
DOI: 10.2196/28415
|View full text |Cite|
|
Sign up to set email alerts
|

The Use of Person-Centered Language in Medical Research Journals Focusing on Psoriasis: Cross-sectional Analysis

Abstract: Background Person-centered language places a person’s identity before any disability or medical condition they may have. Using person-centered language reduces stigma and improves the patient-physician relationship, potentially optimizing health outcomes. Patients with psoriasis often feel stigmatized due to their chronic skin condition. Objective We seek to evaluate the use of person-centered language in psoriasis literature and to explore whether cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In a study examining PCL in alcohol use disorder (AUD) research, Hartwell et al 17 found that nearly 80% of articles contained non-PCL terms. Similarly, in a study investigating PCL use in patients with psoriasis, Ottwell et al 18 found that 68% of articles were not PCL-adherent. The culmination of these findings suggests that the use of stigmatising language may persist throughout many fields of medicine.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In a study examining PCL in alcohol use disorder (AUD) research, Hartwell et al 17 found that nearly 80% of articles contained non-PCL terms. Similarly, in a study investigating PCL use in patients with psoriasis, Ottwell et al 18 found that 68% of articles were not PCL-adherent. The culmination of these findings suggests that the use of stigmatising language may persist throughout many fields of medicine.…”
Section: Discussionmentioning
confidence: 92%
“…With the help of PCL, we can help reduce stigma. As Ottwell et al state, and as we would like to reiterate, ‘non-PCL is most likely not malicious and is often a result of adherence to an unchanged status quo’ 18. While the use of non-PCL has been investigated in publications regarding topics such as AUD,17 dermatology18 and childhood obesity,29 it has yet to be examined among HIV research.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…While both medical standards and social norms are moving away from stigmatizing language regarding individuals and their diagnosis, stigmatizing language still persists within medical literature including publications focused on alcohol use disorder, 29 psoriasis, 30 and amputations 31 With the integration of evidence‐based medicine into medical education and practice, we posit that the translation of medical literature is not only significant upstream mediator of stigma to clinical practice but also foundational to patient care 32 . However, the perpetuation of non‐PCL in obesity‐related literature has allowed for its continuation in medical practice.…”
Section: Discussionmentioning
confidence: 99%